2011
DOI: 10.1523/jneurosci.2209-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dual Gamma Rhythm Generators Control Interlaminar Synchrony in Auditory Cortex

Abstract: Rhythmic activity in populations of cortical neurons accompanies, and may underlie, many aspects of primary sensory processing and short-term memory. Activity in the gamma band (30 Hz up to > 100 Hz) is associated with such cognitive tasks and is thought to provide a substrate for temporal coupling of spatially separate regions of the brain. However, such coupling requires close matching of frequencies in co-active areas, and because the nominal gamma band is so spectrally broad, it may not constitute a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 60 publications
(87 reference statements)
6
87
3
Order By: Relevance
“…Layer 2/3 neurons are strongly connected to layer 5 neurons (38) so we need also to consider any changes in deeper layers with respect to the above layer 2/3 changes. Layer 5 local circuits (at least in auditory cortex) do not appear to support gamma rhythm generation alone (24) and, in contrast to the superficial layers, receive a predominantly inhibitory input from layer 4 (18). No change in layer 5 EPSP strength was seen in the present study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Layer 2/3 neurons are strongly connected to layer 5 neurons (38) so we need also to consider any changes in deeper layers with respect to the above layer 2/3 changes. Layer 5 local circuits (at least in auditory cortex) do not appear to support gamma rhythm generation alone (24) and, in contrast to the superficial layers, receive a predominantly inhibitory input from layer 4 (18). No change in layer 5 EPSP strength was seen in the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…It has been shown that the patterns of postsynaptic excitatory activity in layer 5 pyramidal cells needed to generate inhibitory input plasticityshort bursts of action potentials-need not also modify excitatory input (i.e., inhibitory synaptic potentiation onto pyramidal cells can occur without concomitant excitatory plasticity as seen in the present experiments) (45). Such a pattern of burst outputs is common in this neuron subtype during gamma rhythms in auditory cortex (24). Interestingly, this form of inhibitory synaptic plasticity did not require precise timing of pre-and postsynaptic excitatory neuronal spiking (46), but potently narrowed the integration window for input summation and enhanced output temporal precision once established (45,46).…”
Section: Discussionsupporting
confidence: 50%
“…Both terminologies are appropriate as long as it becomes clear that there are (at least) two other independent slower gamma oscillations <100 Hz in the hippocampus (in this convention, the slow gamma associated with CA3, and the middle gamma associated with mEC). Similar distinctions do possibly apply to neocortical areas such as the mEC (Middleton et al, 2008) and the auditory cortex (Ainsworth et al, 2011; see also Whittington et al, 2010). Calling HFOs ''gamma oscillations'' may be confusing because the latter term has been typically employed to denote an inhibition dependent rhythm (Whittington et al, 2000).…”
Section: Hfos Vs Low-and High-gamma Oscillationsmentioning
confidence: 96%
“…The amount of reproducible temporal structure is astonishing, and the task of charting such structure is by no means finished. Structure found in vitro includes: Multiple mechanistically different versions of a rhythm in the same frequency band (Roopun et al , 2010); Multiple mechanistically different rhythms in the same cortical region (Ainsworth et al , 2011); Different rhythms appearing simultaneously in different cortical layers (Oke et al , 2010; Ainsworth et al , 2012); Different effects of neuromodulators on rhythms in different brain areas (Middleton et al , 2008; Roopun et al , 2008a); Switches in temporal structure with changes in activation (Roopun et al , 2008b); Fast rhythms nested inside slower rhythms (Gloveli et al , 2005; Carracedo et al , 2013); Faster intrinsic rhythms suppressed by slower ones (Pietersen et al , 2014). Some of this structure observed in vitro has also been found in vivo .…”
Section: What Constitutes the Dynome?mentioning
confidence: 99%